Structural and functional characterization of the locus coeruleus in young and late middle-aged individuals - Alexandre Berger; Alexandre Berger; Alexandre Berger; Ekaterina Koshmanova; Elise Beckers; Elise Beckers; Roya Sharifpour; Ilenia Paparella; Islay Campbell; Nasrin Mortazavi; Fermin Balda; Yeo-Jin Yi; et al. (Frontiers in Neuroimaging, 2023)
IntroductionThe brainstem locus coeruleus (LC) influences a broad range of brain processes, including cognition. The so-called LC contrast is an accepted marker of the integrity of the LC that consists of a local hyperintensity on specific Magnetic Resonance Imaging (MRI) structural images. The small size of the LC has, however, rendered its functional characterization difficult in humans, including in aging. A full characterization of the structural and functional characteristics of the LC in healthy young and late middle-aged individuals is needed to determine the potential roles of the LC in different medical conditions. Here, we wanted to determine whether the activation of the LC in a mismatch negativity task changes in aging and whether the LC functional response was associated to the LC contrast.MethodsWe used Ultra-High Field (UHF) 7-Tesla functional MRI (fMRI) to record brain response during an auditory oddball task in 53 healthy volunteers, including 34 younger (age: 22.15y ± 3.27; 29 women) and 19 late middle-aged (age: 61.05y ± 5.3; 14 women) individuals.ResultsWhole-brain analyses confirmed brain responses in the typical cortical and subcortical regions previously associated with mismatch negativity. When focusing on the brainstem, we found a significant response in the rostral part of the LC probability mask generated based on individual LC images. Although bilateral, the activation was more extensive in the left LC. Individual LC activity was not significantly different between young and late middle-aged individuals. Importantly, while the LC contrast was higher in older individuals, the functional response of the LC was not significantly associated with its contrast.DiscussionThese findings may suggest that the age-related alterations of the LC structural integrity may not be related to changes in its functional response. The results further suggest that LC responses may remain stable in healthy individuals aged 20 to 70.